ChemInform Abstract: Growth, Crystal Structure and Optical Properties of a New Layered Fluorine Beryllium Borate, Sr0.23Ca0.77Na2Be2B2 O6F2. Issue 19 (18th April 2013) - Huang, Hongwei; Yao, Wenjiao; Wang, Xiaoyang; Zhai, Naixia; Chen, Chuangtian
Abstract The title fluorine beryllium borate crystal is grown by high temperature solid state reaction of CaCO3, SrCO3, BeO, B2O3, and NaF in stoichiometric amounts (710°C, 48 h).